Exploring Interior Designers' Research Utilization Strategies and Information‐Seeking Behaviors. Issue 2 (17th April 2018) - Huber, Amy
Abstract: Research findings that remain unknown to design practitioners stand little chance of improving their design processes or project outcomes. The research utilization gap is evident from both the perspectives of scholars and design practitioners. While design scholars have long lamented practitioners' apparent indifference toward scholarly research, some interior designers and architects attribute their apathy to irrelevance. The few strategies that have been offered to reconcile this divide largely remain untested. Consequently, little is known about practitioner motivations for seeking information and their patterns of behavior while doing so. This study used Pelz's Research Utilization Strategies and Hëinstrom's Information‐Seeking Behaviors to gain a contemporary understanding of interior designers' information preferences (i.e., their motivations for seeking information and their activities while doing so). Findings stemming from 104 commercial interior designers and managers suggest that designers value information, often seeking sources for their general enlightenment. However, analysis revealed a statistically significant preference for rapid reviewing processes. Differences were also revealed between information preferences and the age and experience of respondents, such that inexperienced designers were more likely to use information to confirm beliefs rather than explore a problem. The apparent dichotomy between interior designers' desire to seek information and their often cursory behaviors while reviewing it, suggests that scholars who aim to share their findings with practitioner audiences may need to reexamine their dissemination strategies. Findings suggest confusion surrounding the ethical and appropriate application of information within project settings and design educators may wish to emphasize the application of research in studio settings.